Despite COVID-19, food consumption remains steady in Addis Ababa, Ethiopia - de Brauw, Alan; Hirvonen, Kalle; Abate, Gashaw T. (International Food Policy Research Institute, 2022)
There is substantial concern that global food insecurity is increasing as a result of the COVID-19 pandemic. Organizations such as the Food and Agriculture Organization of the United Nations (FAO), World Food Programme (WFP), and CGIAR are trying to get a clear picture of the growing challenges people may be facing, but the nature of the pandemic makes data on food security and daily living hard to obtain. Because face-to-face surveys have largely not been possible during the pandemic, much of what we know about actual changes in food security status comes from phone surveys. These surveys suggest large proportions of respondents are facing falling incomes; the World Bank reports declines in incomes and food security where they have conducted phone surveys.